Pore Pressure Prediction Using Velocity-Mean Effective Stress Relationship in Madura Sub-basin, East Java Basin - Indonesia - Sena W Reksalegora; Lambok M. Hutasoit; Agus H. Harsolumakso; Agus M. Ramdhan (Geological Agency, 2022)
DOI:10.17014/ijog.9.2.247-262Pore pressure prediction using velocity-mean effective stress relationship is introduced in Madura Subbasin which is located in a compressional tectonic setting. The new workflow accommodates the three principal stresses, those are vertical stress, maximum horizontal stress, and minimum horizontal stress in a form of mean stress as the compaction main inducing agent. The application of this new workflow has resulted in a more accurate pore pressure prediction where the normally used pore pressure prediction method tends to underestimate the actual data. In Dukuh-1 well, as an example, the pore pressure prediction from the new work flow is able to explain the continuous hole problems such as well flows and well kicks that were recorded during drilling. In MDA-2 well, the new pore pressure prediction closely matches the well data in comparison to the normally used prediction. As a result, a more accurate regional pore pressure prediction map using mean stress is generated to aid both hydrocarbon exploration and development activities in the study area